Service Quality Drives Purchase Decisions and Loyalty through Repeat Purchases: Kualitas Layanan Memengaruhi Keputusan Pembelian dan Loyalitas Melalui Pembelian Berulang - Bintang Anggry Awan Putra Aditya; Minto Waluyo (Universitas Muhammadiyah Sidoarjo, 2025)
(General Background) The increasing competition in Indonesia’s retail sector highlights the critical role of service quality in influencing consumer purchasing behavior. (Specific Background) Faiz Plastic Store Sidoarjo, a retailer of household and packaging products, has experienced a decline in sales performance, allegedly due to deteriorating service quality that affects consumer retention. (Knowledge Gap) Previous studies have confirmed the impact of service quality on purchasing behavior, yet empirical evidence regarding its structural influence on purchase decisions, repeat purchases, and customer loyalty in small-scale retail settings remains limited. (Aims) This study aims to analyze the causal relationship between service quality (Servqual), purchase decisions, repeat purchases, and customer loyalty using Structural Equation Modeling (SEM). (Results) Findings reveal that service quality significantly influences purchase decisions, but purchase decisions do not significantly affect repeat purchases, while repeat purchases have a strong positive effect on customer loyalty. (Novelty) The study develops a structural model that clarifies the indirect mechanism linking Servqual dimensions to loyalty through behavioral intentions. (Implications) The results emphasize that maintaining high service quality should be complemented with loyalty programs, digital engagement, and online ordering systems to ensure customer retention and business sustainability. Highlights: Service quality significantly shapes initial purchasing behavior. Repeat purchases serve as the main driver of customer loyalty. Loyalty programs and digital engagement enhance long-term retention. Keywords: Servqual, Purchase Decision, Repeat Purchase, Customer Loyalty, Retail Service Quality